PENINGKATAN TRANSPARANSI LAPORAN KEUANGAN DAN KINERJA BUMDES - Seswandi, Agus; Burhan, Burhan; Oemar, Fahmi; Bambang, Bambang (Komunitas Manajemen Kompetitif, 2024)
Badan Usaha Milik Desa (BUMDes) are institutions established by the village government to manage businesses owned by the village and aim to improve the welfare of village communities. In practice, BUMDes often face several problems, especially related to transparency and financial report performance. Some of the problems are lack of transparency; Financial reports that should be published to the village community are often not done routinely or completely.; Unclearness in Financial Separation, there is difficulty in separating BUMDes finances from village finances. The next problem is Weak Financial Report Performance caused by; Lack of Management Capacity: Many BUMDes are managed by individuals who lack the ability or knowledge in financial management and accounting. The targets and outputs to be achieved are 1) Increased capacity of BUMDes managers, 2) Increased implementation of a better financial recording system and stricter supervision and audits 3) Changes Better transparency can also be built through routine reporting. The solution is assistance on increasing the capacity of BUMDes managers, 2) Regarding partner problems, efforts need to be made to improve the implementation of a better financial recording system and stricter supervision and audits. The method of implementing the activity consists of mentoring partners. The methods used are 1) interactive discussion. 2) mentoring/training. This mentoring activity succeeded in increasing the understanding of BUMDes administrators about the importance of transparency in financial reports. Through an interactive approach and constructive discussion, participants can better understand the challenges faced and the solutions that can be applied to increase transparency in their BUMDes financial reports. In the future, it is hoped that BUMDes can implement this transparency practice more consistently to build public trust, improve financial performance and ensure the continuity of BUMDes businesses. Keywords: BUMDEs, Transparency, Financial Reports